Synthesis of High-Thermal Stable Titanium Dioxide Nanoparticles - M. Rashidzadeh (International Journal of Photoenergy)
Nanosized crystals of anatase phase TiO2 with high-thermal stability was synthesized in the range of 15–17 nm via sol-gel method using titanium n-butoxide precursor. Synthesize was done at two different temperatures, that is, 200 and 300∘C and the final products were calcined at 400∘C. The final products were characterized by N2 adsorption, X-ray diffraction, FT-IR, and TEM and tested in a photoreactor using fluorescien as model molecule. For thermal stability investigation, the sample prepared at 300∘C was heated up to 800, 850, and 900∘C, the XRD results showed that the synthesized anatase phase was stable up to 850∘C. Photocatalytic activity of the prepared samples showed that the fluorescien degradation followed a pseudo-first-order kinetic.